The call to sell: a qualitative exploration of calling for religiously identified women in multi-level marketing - Jayne, Alexa, author; Dik, Bryan, advisor; Prasad, Joshua, committee member; Tompkins, Sara Anne, committee member; Albert, Lumina, committee member (Colorado State University. Libraries, 2022)
Work is a life domain in which many people perceive a calling. Research on calling reveals that workers who perceive and live out a calling often experience a range of positive outcomes, such as increased work-related and overall life satisfaction and well-being. However, living a calling can also lead to negative outcomes, such as workaholism, burnout, and exploitation. Multi-level marketing (MLM) is a business model that operates via direct selling and network recruitment. This business model has been found to be particularly attractive to women. It has also gained traction within the faith community, with many MLM companies aligning with Christian values and faith communities. This study sought to investigate the sense of calling that religiously identified women who work in Young Living, a leading MLM company in the United States, may experience. Six individuals participated in-depth structured interviews, and transcripts were analyzed using Interpretative Phenomenological Analysis (IPA). Results revealed four domains and multiple themes, including 1) Reasons for Joining (e.g., supplementary income, pipeline of buying to selling, positive previous experiences with product, means to achieve work-life balance, desire to have own business), 2) Sense of Calling (e.g., transcendent summons, desire to educate and share clean products with others, sharing their faith with others, empowering others to become distributors, perceiving multiple callings), 3) Positive Outcomes (e.g., personal and professional growth, belonging to a community of like-minded people, camaraderie with other women in business, positive recognition and social influence, increased religious engagement), and 4) Negative Outcomes associated with the work (e.g., overwhelm and difficulty setting boundaries, moral disagreements with discourse and utilization of certain products, negative perceptions of business structure from others, needing to convince others about usefulness of products). Implications for clinicians, organizations, and future research are explored. Future research is recommended to replicate and validate the results of this study. Research is also recommended to investigate how the results of this study may apply to more diverse samples, utilizing both qualitative and quantitative methods. The results of this study may help to inform clinicians into how one's religious perspective may inform their sense of calling.
Keywords: meaning making; psychology of religion; work as a calling; multilevel marketing; calling; vocational psychology